Comparative Study of Conventional Inverted ILM Flap Covering and ILM Flap Filling Technique in Idiopathic Macular Hole Treatment: A Meta-Analysis and Systematic Review - Mengying Tao; Guoqing Wang; Yueqin Gou; Ming Zhang (Journal of Ophthalmology)
Objective. This meta-analysis was performed to evaluate the anatomical efficacy and functional improvement of the conventional inverted internal limiting membrane (ILM), flap covering technique, and ILM flap filling technique for patients with idiopathic macular hole (MH). Methods. Literature from Pubmed, Embase, Cochrane Central Register of Controlled Trials, and Web of Science were comprehensively retrieved. The primary outcomes included the MH closure rate and postoperative best-corrected visual acuity (BCVA). The secondary outcomes were the proportion of external limiting membrane (ELM) and ellipsoid zone (EZ) defect recovery. Pooled odds ratios (ORs), weighted mean differences (WMDs), and 95% confidence intervals (CIs) were calculated using STATA 17.0 software. Results. 7 studies that contained 139 eyes in the inverted ILM flap covering group and 121 eyes in the ILM flap filling group were selected. Pooled data suggested that the surgical treatment resulted in an overall MH closure rate of up to 97.12% (135/139 eyes) in the inverted ILM flap covering group and 99.17% (120/121 eyes) in the filling group, with no significant difference between the 2 groups (OR = 1.98, 95% CI: 0.55 to 7.09, and P=0.29). Similarly, the 2 techniques demonstrated equal effectiveness on the anatomical closure in MH with the average diameter smaller than 650 μm (OR = 2.17, 95% CI: 0.48 to 9.77, and P=0.31) and larger than 650 μm (OR = 1.58, 95% CI: 0.14 to 17.37, and P=0.71). However, compared with the filling technique, the inverted ILM flap covering technique was superior in postoperative BCVA (WMD = 0.11, 95% CI: 0.04 to 0.18, and P=0.0017) and presented a significantly higher proportion of reconstitution of ELM (OR = 0.02, 95% CI: 0.00 to 0.08, and P<0.0001) and EZ (OR = 0.11, 95% CI: 0.04 to 0.32, and P=0.0001). Conclusion. The inverted ILM flap covering technique was associated with the superior reconstitution of outer layers of the retina, including ELM and EZ, and more improvement in postoperative BCVA than the ILM flap filling technique.